Psychromonas saccharinae sp. nov., Isolated from Marine Macroalga Saccharina japonica - Ying Ouyang; Jiapeng Li; Ruojing Tu; Hao Dong; Xianzhen Zhou; Anyi Hu; Feng Lin; Xiuli Chen; Chenhui Zhong; Jiangwei Li (Current Microbiology, 2026)

Dietary Bacillus sp. ‌Modulates Multi-tissue Metabolism Through Gut Microbiota Remodeling in High-fat Fed Larimichthys crocea - Ruojing Li; Biao Yuan; Xin Yi; Ermei Yin; Bi Huang; Qianwen Min; Jiayu Zhou; Meiqi Lv; Bo Zhang; Na Zhao (Probiotics and Antimicrobial Proteins, 2026)

From morphological constraints to genomic SNPs: Developing population identification methods exemplified by large yellow croaker (Larimichthys crocea) - Zebin Zhou; Xubing Ba; Qianwen Min; Jiayu Zhou; Xin Yi; Ruojing Li; Bi Huang; Na Zhao; Bo Zhang; Songlin Chen (Aquaculture, 2026)

miR-133b regulation of wbp2 in ovaries is conserved among teleosts - Jiayu Zhou; Qianwen Min; Xubing Ba; Zhaoqiu Qu; Zhenjun Zhuang; Biao Yuan; Xin Yi; Ruojing Li; Na Zhao; Bo Zhang (Acta Oceanologica Sinica, 2025)

Taurine related pathways effect the potential domestication of wild Larimichthys crocea adapt to stress environment - Xubing Ba; Zhenjun Zhuang; Zebin Zhou; Jiayu Zhou; Qianwen Min; Biao Yuan; Xin Yi; Ruojing Li; Zhaoqiu Qu; Na Zhao; Bo Zhang (Aquaculture, 2025)

Integrated omics analysis reveals the effect of feeding scarcity on the lipid metabolism and apoptosis in Nibea coibor - Zhaoqiu Qu; Biao Yuan; Ruojing Li; Xubing Ba; Zhenjun Zhuang; Xin Yi; Jiayu Zhou; Qianwen Min; Zhongdian Dong; Na Zhao; Bo Zhang (Aquaculture, 2025)

Host development promotes the early microbiota succession of teleost surpassing dietary management - Na Zhao; Ruojing Li; Xufeng Zhu; Biao Yuan; Chunhua Zhu; Bo Zhang (Aquaculture, 2024)

Phosphorus functionalized tungsten trioxide nanosheets loaded on three-dimensional carbon felt for efficient electrochemical uranium extraction - Zitong Yan; Yujuan Pu; Mingyang Zhang; Ruojing Deng; Fanyue Shi; Haoyuan Li; Tao Duan; Youkui Zhang (Desalination, 2024)

Constructing dendritic arrays composed of copper nanowires loaded with polyaniline for efficient nitrate electroreduction to ammonia - Yi Li; Yujuan Pu; Zitong Yan; Yuhang He; Ruojing Deng; Haoyuan Li; Tao Duan; Youkui Zhang (Journal of Environmental Chemical Engineering, 2024)

Occurrence characteristics and influencing factors of antibiotic resistance genes in rural groundwater in Henan Province - Kai Zhang; Kuangjia Li; Feiyue Hu; Rui Xin; Penglin Fan; Yarou Lu; Ningning Wang; Mengyuan Qin; Ruojing Li (Environmental Science and Pollution Research, 2024)

The feasibility of Chinese mitten crab (Eriocheir sinensis), mandarin fish (Siniperca chuatsi), and mud carp (Cirrhinus molitorella) polyculture and their effects on growth performance, water quality, antioxidant, and nonspecific immunological capacity - Ruojing Li; Mantang Xiong; Wang Li; Wei Li; Jiashou Liu; Tanglin Zhang (Aquaculture International, 2023)

A theoretical study on gas-phase reactions of CF3CH=CF2 with OH: mechanism, kinetics and insights - Peng Zhang; Lu Ma; Haomin Wang; Huirong Li; Ruojing Song; Zhiguo Wang; Yuxi Sun; Yunju Zhang (Journal of Fluorine Chemistry, 2023)

Valuing the coordinated development of urbanization and ecosystem service value in border counties - Zheneng Hu; Jianjiao Gong; Jiaxi Li; Ruojing Li; Zhuoya Zhang; Fanglei Zhong; Chuanhao Wen (Journal of Cleaner Production, 2023)

A review of metal contamination in seagrasses with an emphasis on metal kinetics and detoxification - Yanping Li; Fengyuan Chen; Ruojing Zhou; Xinqing Zheng; Ke Pan; Guanglong Qiu; Zhongjie Wu; Shiquan Chen; Daoru Wang (Journal of Hazardous Materials, 2023)

CAS FGOALS-g3 Model Datasets for the CMIP6 Scenario Model Intercomparison Project (ScenarioMIP) - Ye Pu; Hongbo Liu; Ruojing Yan; Hao Yang; Kun Xia; Yiyuan Li; Li Dong; Lijuan Li; He Wang; Yan Nie; Mirong Song; Jinbo Xie; et al. (Advances in Atmospheric Sciences, 2020)
This paper describes the datasets from the Scenario Model Intercomparison Project (ScenarioMIP) simulation experiments run with the Chinese Academy of Sciences Flexible Global Ocean-Atmosphere-Land System Model, GridPoint version 3 (CAS FGOALS-g3). FGOALS-g3 is driven by eight shared socioeconomic pathways (SSPs) with different sets of future emission, concentration, and land-use scenarios. All Tier 1 and 2 experiments were carried out and were initialized using historical runs. A branch run method was used for the ensemble simulations. Model outputs were three-hourly, six-hourly, daily, and/or monthly mean values for the primary variables of the four component models. An evaluation and analysis of the simulations is also presented. The present results are expected to aid research into future climate change and socio-economic development.

Estimation and characterization of annual precipitation based on spatiotemporal kriging in the Huanghuaihai basin of China during 1956–2016 - Xue Yang; Yong Yang; Ke Li; Ruojing Wu (Stochastic Environmental Research and Risk Assessment, 2020)

Pressure balance and imbalance in the optic nerve chamber: The Beijing Intracranial and Intraocular Pressure (iCOP) Study - Ruowu Hou; Zheng Zhang; Diya Yang; Huaizhou Wang; Weiwei Chen; Zhen Li; Jinghong Sang; Sumeng Liu; Yiwen Cao; Xiaobin Xie; Ruojing Ren; Yazhuo Zhang; et al. (Science China Life Sciences, 2016)